Exploring the interactions between metabolic dysfunction-associated fatty liver disease and micronutrients: from molecular mechanisms to clinical applications - Liu, Yuan; Qin, Xiang; Chen, Tianzhu; Chen, Mengyao; Wu, Liyan; He, Beihui (Frontiers in Nutrition, 2024)
Metabolic (dysfunction)-associated fatty liver disease (MAFLD) has emerged as a significant global health concern, representing a major cause of liver disease worldwide. This condition spans a spectrum of histopathologic stages, beginning with simple fatty liver (MAFL), characterized by over 5% fat accumulation, and advancing to metabolic (dysfunction)-associated steatohepatitis, potentially leading to hepatocellular carcinoma. Despite extensive research, there remains a substantial gap in effective therapeutic interventions. This condition's progression is closely tied to micronutrient levels, crucial for biological functions like antioxidant activities and immune efficiency. The levels of these micronutrients exhibit considerable variability among individuals with MAFLD.Moreover, the extent of deficiency in these nutrients can vary significantly throughout the different stages of MAFLD, with disease progression potentially exacerbating these deficiencies. This review focuses on the role of micronutrients, particularly vitamins A, D, E, and minerals like iron, copper, selenium, and zinc, in MAFLD's pathophysiology. It highlights how alterations in the homeostasis of these micronutrients are intricately linked to the pathophysiological processes of MAFLD. Concurrently, this review endeavors to harness the existing evidence to propose novel therapeutic strategies targeting these vitamins and minerals in MAFLD management and offers new insights into disease mechanisms and treatment opportunities in MAFLD.